Plasma levels of MMP-7 and TIMP-1 in laboratory diagnostics and differentiation of selected histological types of epithelial ovarian cancers - Grażyna Ewa Będkowska; Ewa Gacuta; Monika Zajkowska; Edyta Katarzyna Głażewska; Joanna Osada; Maciej Szmitkowski; Lech Chrostek; Milena Dąbrowska; Sławomir Ławicki (BMC, 2017)
Abstract Background MMP-7 and TIMP-1 may play a role in the pathogenesis of cancer disease. In this study we investigated plasma levels of selected metalloproteinase and its tissue inhibitor in comparison to plasma levels of the commonly accepted tumor markers (CA 125 and HE4) in selected histological types of epithelial ovarian cancer patients as compared to control groups: patients with a benign ovarian tumor and healthy subjects. Plasma levels of MMP-7 and TIMP-1 were determined using ELISA, CA 125 and HE4 - by CMIA methods. Results Plasma levels of all biomarkers studied were significantly higher in ovarian cancer patients as compared to both control groups. MMP-7 demonstrated comparable to HE4 or CA125 values of diagnostic sensitivity (SE: 61%; 68%; 58%, respectively), specificity (SP: 95%; 95%; 98%, respectively), positive (PPV: 93%; 96%; 98%, respectively) and negative predictive values (NPV: 61%; 66%; 60%, respectively) in the groups tested. The combined use of the aforementioned biomarkers resulted in a further increase in diagnostic criteria and AUC, especially in the early stages of the disease. Conclusions These findings suggest the usefulness of combining MMP-7 with CA 125 and HE4 in the diagnosis of epithelial ovarian cancer as a new tumor marker panel.